Pedagang Siomay: a study on the influence of urbanization on the type of work of the head of household in Cisukadana Village, Kadugede District, Kuningan District, West Java - Dede Tresna Wiyanti; Hardian Eko Nurseto (Universitas Padjadjaran, 2018)
ABSTRACTKuningan regency as one of the regencies in West Java Province, is a counter magnet area. This area is expected to absorb the increase of population and give socio-economic service in urbanization process of Jakarta Metropolitan. The main pull factor in the urbanization process is the opportunity to work in the city. This causes the productive workforce go to the city. Although the economic sector that can accommodate labor from the rural is the informal sector, that did not prevent the seasonal workers from Cisukadana went to the city.This research was conducted in Cisukadana Village, Kadugede District, Kuningan Regency. The quantitative method were used in this research. This study aims to illustrate how the urbanization process in megapolitan city of Jakarta can affect the types of work in the village of Cisukadana, Kadugede district, Kuningan regency, West Java. Based on the findings, it appears that almost half of the total household heads in Cisukadana Village are seasonal workers, working in the informal sector in Jakarta. And of the total number of workers, most of them work as pedagang siomay.